Defining "Normal" Static and Dynamic Spinopelvic Characteristics: A Cross-Sectional Study. Issue 3 (5th July 2022) - Verhaegen, Jeroen C.F.; Innmann, Moritz; Alves Batista, Nuno; Dion, Charles-Antoine; Horton, Isabel; Pierrepont, Jim; Merle, Christian; Grammatopoulos, George
Abstract : Background: Spinopelvic characteristics influence the hip's biomechanical behavior. However, there is currently little knowledge regarding what "normal" characteristics are. This study aimed to determine how static and dynamic spinopelvic characteristics change with age, sex, and body mass index (BMI) among well-functioning volunteers. Methods: This was a cross-sectional cohort study of 112 asymptomatic volunteers (age, 47.4 ± 17.7 years; 50.0% female; BMI, 27.3 ± 4.9 kg/m 2 ). All participants underwent lateral spinopelvic radiography in the standing and deep-seated positions to determine maximum hip and lumbar flexion. Lumbar flexion (change in lumbar lordosis, ∆LL), hip flexion (change in pelvic-femoral angle, ∆PFA), and pelvic movement (change in pelvic tilt, ΔPT) were determined. The hip user index, which quantifies the relative contribution of the hip to overall sagittal movement, was calculated as (∆PFA/[∆PFA + ∆LL]) × 100%. Results: There were decreases of 4.5° (9%) per decade of age in lumbar flexion (rho, −0.576; p < 0.001) and 3.6° (4%) per decade in hip flexion (rho, −0.365; p < 0.001). ∆LL could be predicted by younger age, low standing PFA, and high standing LL. Standing spinopelvic characteristics were similar between sexes. There was a trend toward men having less hip flexion (90.3° ± 16.4° versus 96.4° ± 18.1°; p = 0.065) and a lower hip user index (62.9% ± 8.2% versus 66.7% ± 8.3%; p = 0.015). BMI weakly correlated with ∆LL (rho, −0.307; p = 0.011) and ∆PFA (rho, −0.253; p = 0.039). Conclusions: Spinopelvic characteristics were found to be age, sex, and BMI-dependent. The changes in the lumbar spine during aging (loss of lumbar lordosis and flexion) were greater than the changes in the hip, and as a result, the hip's relative contribution to overall sagittal movement increased. Men had a greater change in posterior pelvic tilt when moving from a standing to a deep-seated position in comparison with women, secondary to less hip flexion. The influence of BMI on spinopelvic parameters was low.